The changing water cycle: the need for an integrated assessment of the resilience to changes in water supply in High‐Mountain Asia. (24th October 2017) - Quincey, Duncan; Klaar, Megan; Haines, Daniel; Lovett, Jon; Pariyar, Bishnu; Gurung, Gehendra; Brown, Lee; Watson, Cameron; England, Matthew; Evans, Barbara
Abstract : Water sourced from Asian mountains is vital to the survival of an estimated 1.4 billion people, but current and anticipated changes in snow, ice cover, and precipitation patterns may threaten these supplies and, in turn, the food security of tens of millions of people. Despite the severity of this developing environmental hazard, the relative importance of each component of the water cycle still needs more detailed study so that those communities who will experience the greatest extremes in supply can be identified. Specifically, data showing how the contribution of meltwater varies with increasing distance downstream are lacking for many mountain catchments, although the use of stable isotope tracers provides some hope in this regard. Imprinted on regional‐scale hydroclimatological controls of water availability are local‐scale cultural beliefs and practices that have evolved over centuries, which determine who is able to access water supplies, for how long, and for what purpose. Building the resilience of human populations and the environment to future changes in water supply therefore depends on effective interdisciplinary team working to develop an understanding of the complex interactions between physical, socioeconomic, cultural, and historical factors, and that can only be properly realized if local communities are considered as an integral part of the research team. Developing simple and practical methods for water management, storage, and societal adaptation that are appropriate to the socioeconomic and political conditions of mountain‐dwelling communities will only be sustainable if they are built on this integrated knowledge base. WIREs Water 2018, 5:e1258. doi: 10.1002/wat2.1258 This article is categorized under: Engineering Water > Planning Water Human Water > Water Governance Science of Water > Water and Environmental Change Abstract : Building resilience to changes in Asian water supply will depend on scientific knowledge, social understanding, and an appreciation of environmental history.